Nutritional Intervention Strategies Using Dietary Antioxidants and Organic Trace Minerals to Reduce the Incidence of Wooden Breast and Other Carcass Quality Defects in Broiler Birds - Kuttappan, Vivek A.; Manangi, Megharaja; Bekker, Matthew; Chen, Juxing; Vazquez-Anon, Mercedes (Frontiers in Physiology, 2021)
Wooden breast (WB) is a degenerative myopathy seen in modern broiler birds resulting in quality downgrade of breast fillets. Affected filets show increased toughness both before as well as after cooking and have decreased water holding capacity and marinade pick up compared to normal fillets. Although the exact etiology is unknown, the circulatory insufficiency and increased oxidative stress in the breast muscles of modern broiler birds could be resulting in damage and degeneration of muscle fibers leading to myopathies. Three independent experiments were conducted to evaluate the effect of various dietary interventions on the incidence of WB when birds are exposed to oxidative stress associated with feeding oxidized fat and mild heat stress. Feed additives such as dietary antioxidant [Ethoxyquin (ETX)], mineral methionine hydroxy analog chelate (MMHAC) of Zn, Cu, and Mn, and organic selenium (Org Se) were tested at recommended levels. In experiment 1, ETX reduced (P < 0.05) the incidence of severe WB induced by oxidized fat diet. The magnitude of improvement in percentage of normal (no WB) filets and reduction in muscle lipid peroxidation was greater (P < 0.05) when ETX and MMHAC were fed together as shown by experiment 2. In birds exposed to mild heat stress (Experiment 3), feeding MMHAC by itself reduced (P < 0.05) tissue damage by reducing incidence of tibial head lesions, skin scratches, breast blisters, in addition to increasing the incidence of normal (no WB) fillets. When MMHAC was combined with ETX and Org Se, further improvement (P < 0.05) in normal (no WB) filets was observed. In summary, under different oxidative stress conditions, dietary intervention programs that contain ETX, MMHA-Zn, -Cu, and -Mn and Org Se can improve performance and increase carcass integrity, reducing problems, such as WB, either independently or with additive effect. This effect is most likely attained by simultaneously improving the exogenous and endogenous antioxidant status, reducing oxidative stress, and improving tissue healing process of the bird.